(untitled) (Journal of Foreign Language Studies, 2024)
In the Japanese word class system, personal pronouns (addressing pronouns) account for a small number, and have distinctly different usage from Vietnamese personal pronouns. When using Japanese personal pronouns, Vietnamese students encounter a number of difficulties which commonly originate from not only the linguistic-cultural characteristics between the two languages, but also the specific communication styles of Japanese language. Therefore, this article clarifies characteristics of personal pronouns in Japanese in comparison with Vietnamese, and analyses equivalent types of translation of first-person pronouns from Japanese to Vietnamese, aiming to improve the quality of teaching/learning Japanese in general and teaching/learning translation in particular.